Optimizing Silage Quality: Best Practices for Maximum Nutrient Retention and Sustainable Dairy Development - Shilpi Islam; Md. Emran Hossain (International Journal of Nutritions, 2025)
Silage is a critical component in dairy production systems, offering a consistent and high-quality feed source throughout the year. Optimizing silage quality begins in the field, requiring strategic practices to maximize nutrient retention and support sustainable dairy development. This study reviews best practices across silage production stages, including crop selection, timely harvesting, precise chopping, controlled fermentation, and efficient storage techniques. Emphasis is placed on achieving the ideal moisture content, reducing oxygen exposure during ensiling, and employing additives to enhance fermentation and preserve feed quality. Innovative approaches, such as the integration of precision agriculture and sustainable practices, are highlighted for reducing losses and environmental impact. Properly managed silage improves animal health, performance, and milk production, directly contributing to resilient dairy systems. The interplay between silage quality and economic sustainability is also explored, offering insights into balancing cost-effectiveness with nutritional excellence. By implementing these strategies, producers can enhance feed efficiency, reduce dependency on external feed inputs, and promote long-term sustainability in dairy farming. This review underscores the importance of field-level practices and advanced management strategies in delivering high-quality silage while ensuring environmental and economic viability for the dairy sector.
Keywords: Fermentation; Sustainable farming; additives; compaction; dairy sustainability; forage quality; moisture content; silage storage